Canonical-dissipative limit cycle oscillators with a short-range interaction in phase space - Mongkolsakulvong, S.; Frank, T.D. (Condensed Matter Physics, 2010)
We consider limit cycle oscillators in terms of canonical-dissipative systems that exhibit a short-range interaction in velocity and position space as described by the Dirac delta function. We derive analytical expressions for stationary distribution functions in phase space and energy space and propose a numerical simulation scheme for the simulation of the many body system as well. We show that the short-range interaction squeezes or stretches energy distribution functions depending on whether the interaction can be regarded as attractive or repulsive. In addition to the interaction effect, we show that energy distribution functions become narrower when limit cycle attractors become stronger. Finally, energy distributions become broader when the pumping energy is increased. The latter effect however disappears in the high energy domain. Розглянуто граничні циклічні осцилятори в термінах канонічно-дисипативних систем, які демонструють короткосяжну взаємодію у швидкісному та позиційному просторі, що описаний дельта-функцією Дірака. Виведено аналітичні вирази для стаціонарних функцій розподілу у фазовому просторі та енергетичному просторі та запропоновано числову симуляційну схему для моделювання багаточастинкової системи. Показано, що короткосяжна взаємодія стискає чи розтягує енергетичні функції розподілу залежно від того, чи взаємодію можна вважати притягальною, чи відштовхувальною. Крім впливу взаємодії, показано, що енергетичні функції розподілу стають вужчими, якщо межа циклічних атракторів стає сильнішою. Накінець, енергетичні розподіли стають ширшими з ростом енергії накачки. Цей ефект, проте, зникає у високоенергетичній області.